Pemberdayaan Ekonomi Masyarakat Melalui Pelatihan Pengembangan Kewirausahaan BSI Link - Wani, Cut Eva; Ismail; Zubaili (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Community economic empowerment is an important aspect in the development of a region. In the context of Peureulak City, community economic empowerment is carried out through entrepreneurship and business development training programs organized by BSI Link. This program aims to increase participants' knowledge, skills, and economic independence, so that they can develop successful businesses and contribute to local economic growth. The method of activity used in this program includes identification of needs, implementation of training, assistance and mentoring, field visits, as well as evaluation and monitoring. By participating in this program, participants gain knowledge about the basics of business, financial management, marketing, and business development strategies. The results of the activities of this training program include increasing the knowledge and skills of participants, developing solid business plans, increasing economic independence, increasing business competitiveness, creating jobs, collaboration and business networks, as well as the impact on sustainable development. Thus, this program has the potential to make a significant contribution to community economic empowerment and sustainable economic growth in Peureulak City. In conclusion, the BSI Link entrepreneurship and business development training program in Peureulak City has clear objectives and structured activity methods. Through this program, participants gain knowledge and skills that will enable them to develop successful businesses and contribute to local economic growth. This program also has the potential to have a positive impact on community economic empowerment and sustainable development.